Extracellular vesicles from subjects with COPD modulate cancer initiating cells phenotype through HIF-1α shuttling - Petraroia, Ilaria; Ghidotti, Patrizia; Bertolini, Giulia; Pontis, Francesca; Roz, Luca; Balsamo, Melissa; Suatoni, Paola; Pastorino, Ugo; Ferretti, Anna Maria; Sozzi, Gabriella; Fortunato, Orazio (Cell death & disease, 2023)
Chronic obstructive pulmonary disease (COPD) is a risk factor for lung cancer development. COPD induces activation of hypoxia-induced signaling, causing remodeling of surrounding microenvironmental cells also modulating the release and cargo of their extracellular vesicles (EVs). We aimed to evaluate the potential role of circulating EVs from COPD subjects in lung cancer onset. Plasma - EVs were isolated by ultracentrifugation from heavy smoker volunteers with (COPD-EVs) or without (heavy smoker-EVs, HS-EV) COPD and characterized following MISEV guidelines. Immortalized human bronchial epithelial cells (CDK4, hTERT-HBEC3-KT), genetically modified with different oncogenic alterations commonly found in lung cancer (sh-p53, KRAS V12 ), were used to test plasma-EVs pro-tumorigenic activity in vitro. COPD-EVs mainly derived from immune and endothelial cells. COPD-EVs selectively increased the subset of CD133 + CXCR4 + metastasis initiating cells (MICs) in HBEC-sh-p53-KRAS V12high cells and stimulated 3D growth, migration/invasion, and acquisition of mesenchymal traits. These effects were not observed in HBEC cells bearing single oncogenic mutation (sh-p53 or KRASV12). Mechanistically, hypoxia-inducible factor 1-alpha (HIF-1α) transferred from COPD-EVs triggers CXCR4 pathway activation that in turn mediates MICs expansion and acquisition of pro-tumorigenic effects. Indeed, HIF-1α inhibition or CXCR4 silencing prevented the acquisition of malignant traits induced by COPD-EVs alone. Hypoxia recapitulates the effects observed with COPD-EVs in HBEC-sh-p53-KRAS V12high cells. Notably, higher levels of HIF-1α were observed in EVs from COPD subjects who subsequently developed cancer compared to those who remained cancer-free. Our findings support a role of COPD-EVs to promote the expansion of MICs in premalignant epithelial cells through HIF-1α-CXCR4 axis activation thereby potentially sustaining lung cancer progression.